2013
DOI: 10.4102/sajhrm.v11i1.495
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between servant leadership, affective team commitment and team effectiveness

Abstract: Orientation: Value-based leadership practices play a critical role in teamwork in high-performance organisations. Research purpose: The aim of the study was to empirically validate a theoretical model explicating the structural relationships between servant leadership, affective team commitment and team effectiveness. Motivation for the study: The increased eliance on teams for production calls for an analysis of the role of follower-focused leadership practices in enhancing eam effectiveness.Research design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 31 publications
(61 reference statements)
3
20
0
Order By: Relevance
“…In a belief that social media has brought great cohesiveness among employees, respondents felt positive by revealing a high percentage of agreement. Mahembe and Engelbrecht (2013) are in agreement as well with this finding by pointing out that "communication of the team's mission and goals with proper feedback enhances cohesive relationships amongst team members". This study revealed a high percentage of the majority of respondents who were in agreement that social media has created online communities that can be easily managed.…”
Section: Research Findingssupporting
confidence: 87%
“…In a belief that social media has brought great cohesiveness among employees, respondents felt positive by revealing a high percentage of agreement. Mahembe and Engelbrecht (2013) are in agreement as well with this finding by pointing out that "communication of the team's mission and goals with proper feedback enhances cohesive relationships amongst team members". This study revealed a high percentage of the majority of respondents who were in agreement that social media has created online communities that can be easily managed.…”
Section: Research Findingssupporting
confidence: 87%
“…Furthermore, the structural model describes relationships between latent variables, and the measurement model describes the relationship between the latent variables and their corresponding indicators (Diamantopoulos and Siguaw, 2000). Finally, in SEM, the implied covariance matrix resulting from the model is then compared with the observed covariance matrix inputted as data to determine model fit (Mahembe and Engelbrecht, 2013).…”
Section: Data Collection Process and Data Analysismentioning
confidence: 99%
“…Because a team cannot perform well without managing team conflict effectively (de Wit et al, 2012 ; Bradley et al, 2015 ), it is critical to understand how team conflict influences team dynamics and its success. Although team commitment has been recognized as one of the critical determinants of team success (Kukenberger et al, 2012 ; Mathieu and Gilson, 2012 ; Mahembe and Engelbrecht, 2013 ), there still has been a paucity of studies investigating the relationship between conflict and team commitment. To answer this call, this study examines the relationships between different types and levels of conflict and team commitment.…”
Section: Introductionmentioning
confidence: 99%